Quality of root fillings performed with two root filling techniques. An in vitro study using micro-CT. (May 2013) - Moeller, L.; Wenzel, A.; Wegge-Larsen, A. M.; Ding, M.; Kirkevang, L. L.
Abstract Objective. The aim of this study was to compare the presence of voids in root fillings performed in oval and ribbon-shaped canals with two root filling techniques, lateral compaction technique (LCT) or hybrid technique (HT), a combination of a gutta-percha masterpoint and thermoplastic gutta-percha. Furthermore, the obturation time for the two techniques was evaluated. Materials and methods. Sixty-seven roots with oval and ribbon-shaped canals were prepared using Profile Ni-Ti rotary files. After preparation, the roots were randomly allocated to two groups according to root filling technique. All roots were filled with AH plus and gutta-percha. Group 1 was filled using LCT (n = 34) and group 2 was filled using HT (n = 33). The obturation time was measured in 30 cases evenly distributed between the two techniques. Voids in relation to the root canal fillings were assessed using cross-section images from Micro-computed Tomography scans. Results. All root canal fillings had voids. Permutation test showed no statistically significant difference between the two root filling techniques in relation to presence of voids (p = 0.092). A statistically significant difference in obturation time between the two techniques was found (p < 0.001). Conclusion. The present study found no statistically significant difference in percentage of voids between two root filling techniques. A 40% reduction in obturation time was found for the HT compared to the LCT.